Technical change, income distribution, and profitability in multisector linear economies - Weikai Chen (University of Massachusetts, Department of Economics, 2019)
This paper analyzes the effect of technical change on income distribution and profitability by comparing the long-run outcomes defined by a uniform profit rate in a multisector linear economy. We study three scenarios with (i) fixed real wage; (ii) fixed profit rate; or (iii) fixed wage-profit ratio, and show that any viable capital- using and labor-saving technical change itself (in the absence of power change) would bring about a fall in the rate of profit. Profit rate would not rise unless the technical change is so power-biased against the working-class that the wage-profit ratio can not be maintained. Our result conclusively supports the argument of the falling rate of profit due to a rising organic composition of capital as an underlying economic force.
Keywords: B51; D33; D57; 330; Technical Change; Falling Rate of Profit; Okishio Theorem